The Outcome of Biofeedback Muscle Re-Education after Brachial Plexus Reconstruction: a Case Series - Arfianti, Lydia; Haryadi, Ratna Darjanti (Surabaya Physical Medicine and Rehabilitation Journal, 2020)
The purpose of this report was to evaluate the outcome of biofeedback muscle re-education after brachial plexus reconstruction. A case series was conducted based on registry data of Rehabilitation Outpatient Clinic. A total of 20 subjects underwent surgical reconstruction to restore elbow flexion in the period of 2012-2014 were included in the study. All 20 subjects received biofeedback muscle re-education until end June 2015 (data extraction). Oucome measures were time to recovery (months) after surgical reconstruction and patients' compliance. Recovery is considered when muscle contraction of biceps (nerve transfer) and gracilis (free functional muscle transfer/ FFMT) are â‰¥ 100Î¼V, recorded using EMG-surface electrode. Of 4 subjects underwent nerve transfer, all showed recovery with median time of 9 months. Of 16 subjects underwent FFMT, 5 showed recovery with median time of 9 months. The majority of subjects in both groups could comply with once in 2 weeks rehabilitation program.